Peran Etika Profesional dalam Membentuk Kualitas Manajemen Pendidikan Pondok Pesantren Darul Ma’arif Kabupaten Rejang Lebong - Aprida, Oma; Warsah, Idi; Nurjannah, Nurjannah; Fajariah, Fajariah; Rahayu, Pebbi Tri Indah; Herawati, Herawati; Rahmawati, Taniasari; Saputri, Elsa (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This research aims to analyze the role of educators' professional ethics. Apart from that, this research also aims to determine the quality of education management at the Darul Ma'arif Islamic Boarding School in Rejang Lebong. This research uses a qualitative research approach. Data collection uses in-depth interview techniques and documentation. The data analysis technique uses a conclusion drawing technique by identifying various special characteristics of a message in an objective, systematic and generalist manner. The research results show that the professional ethical role of educators in Islamic boarding schools has been well developed. Professional ethics have been determined based on the principal's policy when determining the curriculum and recruiting teaching staff. The boarding school leadership determines the quality components and quality of activities as well as the activity implementers who can manage the education management at the Darul Ma'arif Rejang Lebong Islamic Boarding School. This is proven to be able to apply the professional ethical role of educators well. This research also found that the quality of education management at the Darul Ma'arif Rejang Lebong Islamic Boarding School is running well, which can be seen from the activities that have been carried out. There are regulations for teaching staff and students who have good consistency and direction in carrying out professional education management.​